The tailor of Panama [videorecording (DVD)] - Boorman, John, 1933-; Brosnan, Pierce; Rush, Geoffrey, 1951-; Curtis, Jamie Lee, 1958-; Le Carré, John, 1931- (Columbia TriStar Home Entertainment, 2001)
Harry, an ex-con turned tailor to the rich and infamous, is married to Louisa, who is smart and sexy. Andy is a suave and ruthless British spy, who had best come through this time, who forces Harry to eavesdrop on the powerful politicians he clothes. Harry's talent for storytelling is not only taken as truth, but sets off a series of events that threatens to destroy everything most important in his life.